Pre-/post-functionalization in dipyrrin metal complexes - antitumor and antibacterial activity of their glycosylated derivatives - Senge, Mathias (My University, 2018)
A post-functionalization route to tris(dipyrrinato) metal complexes is presented giving access to a range of new complexes relevant in the context of medicinal inorganic chemistry. A pentafluorophenyl group in the meso-position of the dipyrrin ligand serves as an anchor for the connection with alcohols and thiocarbohydrates. The photochemotherapeutic activity of the complexes has been assessed in cellular assays with tumor cell lines and against the Gram-positive bacterium S. aureus. Finally, it is shown that this post-functionalization is also applicable to other dipyrrinato metal complexes.
Dalton Trans
PUBLISHED
Keywords: Dipyrrin metal complexes; Tumour cells; S. aureus